2021
DOI: 10.3390/w13050608
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimizing of NH4+ Removal from Stormwater by Coal-Based Granular Activated Carbon Using RSM and ANN Coupled with GA

Abstract: As a key parameter in the adsorption process, removal rate is not available under most operating conditions due to the time and cost of experimental testing. To address this issue, evaluation of the efficiency of NH4+ removal from stormwater by coal-based granular activated carbon (CB-GAC), a novel approach, the response surface methodology (RSM), back-propagation artificial neural network (BP-ANN) coupled with genetic algorithm (GA), has been applied in this research. The sorption process was modeled based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The research showed that in response surface analysis if the contour shape is elliptic, it indicates significant interaction between the factors, while the opposite is true for a circle. 51 As can be seen intuitively from the contour plot, the interaction between the two factors is relatively significant. There is an optimal SDBS removal area, that is, the area with a contact time of 120–180 min and adsorbent dosage of 70–90 g L −1 , with SDBS removal efficiency of over 90% .…”
Section: Resultsmentioning
confidence: 90%
“…The research showed that in response surface analysis if the contour shape is elliptic, it indicates significant interaction between the factors, while the opposite is true for a circle. 51 As can be seen intuitively from the contour plot, the interaction between the two factors is relatively significant. There is an optimal SDBS removal area, that is, the area with a contact time of 120–180 min and adsorbent dosage of 70–90 g L −1 , with SDBS removal efficiency of over 90% .…”
Section: Resultsmentioning
confidence: 90%
“…The benefits of using RSM for modelling and optimization studies include: (i) it allows for a reduced number of experimental trials vis-à-vis the conventional method of one factor at a time; (ii) it integrates mathematical modeling and experimental design; (iii) it possesses the ability to analyze the interaction of process variables with visual elucidation in spite of the inherent complexity; (iv) it has the capacity of high reasonable optimization degree and (v) it exists in varieties of classes such as Box-Behnken design (BBD), central composite design (CCD), hybrid design, three-level factorial design among others, that suit specific demands [54][55]. To improve the performance of RSM in achieving global optimization, the evolutionary algorithm such as the genetic algorithm, one of the choicest and most popular algorithms, is employed [56]. The adaptive neuro-fuzzy inference logic system or adaptive network-based fuzzy inference logic system (ANFILS) is a part of artificial intelligence (AI) algorithms that map input to output data with high precision accuracy.…”
Section: Cadmium Ionsmentioning
confidence: 99%
“…ANN has been widely used due to its suitability for modeling and simulation of various processes in real engineering applications [9]. ANN does not require a mathematical description of the phenomena in the process, so the simulation of the complicated systems could be performed more efficiently [10].…”
Section: Introductionmentioning
confidence: 99%